Determination of the total content of flavonoids in herbal mixtures with anti-diabetic activity - A. Savych (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Diabetes mellitus is an important social and medical problem, as it causes the development of dangerous complications that lead to disability and mortality. This disease is characterized by a multi-vector pathogenesis that requires a comprehensive approach to treatment. Due to the use of mixtures of medicinal plants in the treatment of diabetes, it is possible to cover all aspects of the development of this disease and its complications, because the combination of different medicinal plants contain more biologically active substances that affect all parts of the pathogenetic mechanism of diabetes mellitus and its complications. Plant biocompounds have a wide range of pharmacological action and various mechanisms of influence on the development of diabetes and diabetic angiopathies (inactivation of the antioxidant defense system, activation of lipid peroxidation and the development of oxidative stress). In addition, the niche of the pharmaceutical market of Ukraine with phytomixtures is almost empty.